Maximizing Retreaded Tire Hardness: An Experimental Investigation - Putri, Wahyu Handayani; Afrinaldi, Feri; Taufik, Taufik; Fernando, Ramadhan Rizki (METAL: Jurnal Sistem Mekanik dan Termal, 2024)
Tires are vehicle parts that have a significant economic impact. When the tires reach their end-of-life, they can be retreaded for further use. A company in Padang, Indonesia, manufactures retreaded tires with hardness specifications of at least 61 Shore A. The technology used by the company is the hot cure retreading. Historical data showed that the process produced 7% of defective tires and cost the company $16 per unit of defective tires. It was identified that curing temperature, mold pressure, inner tube pressure, curing time, and fuel type mixed with adhesive affect tires’ hardness. This paper aims to find the best combination of the above parameters so that the hardness of the retreaded tires is maximized. Experiments were performed, and the Taguchi method was employed to design the experiments. Since the experiments have five factors, and each involves two levels, the degree of freedom of the experiments is five. There were three replications for each treatment. Thus, an L8 orthogonal array was selected. The experimental results showed that the best combination of factors is curing temperature at 140 ˚C, mold pressure at 4 bar, inner tube pressure at 8 bar, curing time for 2 hours, and fuel mixed with adhesive was SBP. The above combination was predicted to produce an average hardness of 63.10 Shore A. A confirmation experiment was then performed by applying the above combination of factors, which resulted in an average hardness of 63.15 Shore A and no retreaded tires having hardness below 61 Shore A.